Pengendalian Kualitas Produk Arummanis dengan Peta Kendali P dan Diagram Fishbone di UMKM Arummanis AT - Aini, Lulu Qurrotul; Sukanta, Sukanta (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
UMKM arummanis AT is an UMKM that produces traditional food, namely arummanis or what is often called grandmother's hair. UMKM arummanis AT often experience defects during arummanis production, which has an impact on sales of the arummanis. The defect in AT's arummanis product is that the arummanis often clumps which makes it difficult to package and results in the arummanis being unfit for sale. The method used is a P control chart and also a fishbone diagram. The results of the research show that the highest proportion of defects is 0.00134 and the lowest proportion of defects is 0.00067 with a center line (CL) of 0.000912. The fishbone diagram shows the factors that cause defects in Arummanis products which are influenced by machine, method, human, environmental and material factors. The conclusion obtained in this research is that according to the P control line analysis, the research results show that 1 point of Arummanis error exceeds the control limit, which is then corrected. The solution to minimize the occurrence of defective products in Arummanis is by creating work SOPs, carrying out routine maintenance, maintaining cleanliness by creating a cleaning schedule, and also providing job training to workers. Keywords : Defective Products, Fishbone Diagram, P Control Chart, Quality.